(untitled) - Churchill, Winston S. (Boston, 1948)
The Gathering Storm, 1948, by Winston S. Churchill. Part of his Second World War series (all others in the series are listed seperarately). Red hardcover book with black title blocks, 784 pages, published by Houghton Mifflin Company.
Keywords: World war, 1939-1945,World war, 1939-1945; Great britain